Perkembangan dan Tantangan Halal Fashion Indonesia Dalam Menjadi Produsen Utama Industri Halal Global - Agus Suaidi Hasan; Baitul Hamdi (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2022)
The purpose of this research is to find out the developments and challenges faced in the halal fashion industry in Indonesia. This research is library research using a qualitative approach. This research was conducted by reading, studying, and analyzing various existing literature, in the form of books, journals, news and research results. The results of the study show that the development of halal fashion in Indonesia continues to increase and progress from year to year and has a positive impact on Indonesia's economic growth. However, behind its development, there are challenges that must be faced by Indonesia to become the center of global halal fashion, fierce competition with foreign countries, the absence of halal competition that applies globally, categorization of halal fashion that is still united with general or conventional fashion, there are still problems in The JPH Law is still low and lacks raw materials, only the competitive spirit of the Indonesian people, and adapting to the COVID-19 pandemic